Neighbourhood regeneration and place leadership: Lessons from Groningen and Birmingham - van Bortel, Gerard; Mullins, David (A+BE | Architecture and the Built Environment, 2016)
The concept of place leadership is new and relatively untheorised in England (but see Gibney & Murie, 2008; Gibney, Copeland & Murie, 2009; Mabey & Freeman, 2010), and has not been explicitly formulated in the Netherlands. However, a related stream of practice and analysis around partnerships (Sullivan & Skelcher, 2002) and network governance (Kickert, Klijn & Koppenjan, 1997; Rhodes, 1997; Koppenjan & Klijn, 2004) is already well-established in both countries and has framed our earlier work on neighbourhood regeneration and housing (Mullins & Rhodes, 2007; Van Bortel and Mullins, 2009; Van Bortel, Mullins & Rhodes, 2009). This article explores connections between place leadership and network governance concepts to identify a set of themes that are then used to explore research evidence on neighbourhood regeneration and the role played by third- sector housing organisations in two cities: Groningen in the north of the Netherlands and Birmingham in the English Midlands. While our research has a particular focus on the housing sector and the role of housing associations (HAs), the regeneration task that our case study organisations set themselves has taken them well beyond ‘bricks-and-mortar’. This requires them to collaborate with municipal authorities and a wide range of partners who contribute to the wellbeing of places and people. We explore the role played by HAs in regeneration partnerships and the implications of place-shaping and network governance.